INCREASED EFFICIENCY FERTILIZERS IN ARABICA COFFEE GROWTH IN VALE DO RIBEIRA, SP - DE CARVALHO, Alex Mendonça [UNESP]; DE GODOY, Leandro José Grava [UNESP]; Silveira, Ariel Moraes [UNESP]; Gonze, Fernanda de Barros [UNESP]; DE FREITAS, Ana Flávia (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2024)
Controlled-release fertilizers have been increasingly used. This study aimed to evaluate and adapt new technologies applied via soil for sustainable coffee production, in order to generate information that contribute to the technical innovation of the crop for the Vale do Ribeira region. The experiment was set at UNESP, in Registro – SP. The experimental design was in randomized blocks. The experiment consisted of eight treatments with four replications, with plots of six plants. Four doses (200, 300, 400 and 500 kg ha-1) of a mixed fertilizer 20-05-20 were used, with controlled release in six months, intended for coffee trees in formation and production, compared to the dose of 500 kg ha-1 of the conventional mixed fertilizer 20-05-20, ammonium sulfate and calcium nitrate with boron, in addition to a control treatment, which did not receive NPK fertilization. The cultivar used was ‘Obatã IAC 1669’ in 3.0 x 0.6 m spacing. The following characteristics were evaluated: number of plagiotropic branches, number of nodes of plagiotropic branches, stem diameter, plant height and yield, in two harvest periods, besides the surface chemical characteristic of the soil. Increasing the dose of the slow-release fertilizer leads to greater plant growth; the coffee plant presents a highly responsive behavior to the increase in fertilizer doses in relation to nitrogen, and the use of the slow-release fertilizer Agroblen (20-05-20) 100% and ammonium sulfate + SS + KCl allows greater yield.
Keywords: Controlled-Release Fertilizers; Nutritional Analysis; Plant Growth; Yield